Investigating the alterations of endocannabinoidome signaling in the human small intestine in the context of obesity and type 2 diabetes - Volatiana Rakotoarivelo; Bénédicte Allam-Ndoul; Cyril Martin; Laurent Biertho; Vincenzo Di Marzo; Nicolas Flamand; Alain Veilleux (Heliyon, 2024)
Background: Human studies have linked obesity-related diseases, such as type-2 diabetes (T2D), to the modulation of endocannabinoid signaling. Cannabinoid CB1 and CB2 receptor activation by the endocannabinoids (eCBs) 2-arachidonoylglycerol (2-AG) and N-arachidonoylethanolamine (AEA), both derived from arachidonic acid, play a role in homeostatic regulation. Other long chain fatty acid-derived endocannabinoid-like molecules have extended the metabolic role of this signaling system through other receptors. In this study, we aimed to assess in depth the interactions between the circulating and intestinal tone of this extended eCB system, or endocannabinoidome (eCBome), and their involvement in the pathogenesis of diabetes. Methods: Plasma and ileum samples were collected from subjects with obesity and harboring diverse degrees of insulin resistance or T2D, who underwent bariatric surgery. The levels of eCBome mediators and their congeners were then assessed by liquid chromatography coupled to tandem mass spectrometry, while gene expression was screened with qPCR arrays. Findings: Intestinal and circulating levels of eCBome mediators were higher in subjects with T2D. We found an inverse correlation between the intestinal and circulating levels of monoacylglycerols (MAGs). Additionally, we identified genes known to be implicated in both lipid metabolism and intestinal function that are altered by the context of obesity and glucose homeostasis. Interpretation: Although the impact of glucose metabolism on the eCBome remains poorly understood in subjects with advanced obesity state, our results suggest a strong causative link between altered glucose homeostasis and eCBome signaling in the intestine and the circulation.